Membaca Perempuan Dalam Kumpulan Cerpen Perempuan yang Menunggu Karya Dorothea Rosa Herliany - Laura Andri Retno M (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Positioning yourself as a woman by feeling all her existence and helplessness will make us able to read the text in a literary work of women. Literary works which written by female authors usually present messages and ideas contrary to the patriarchal system. If the reader simply places himself as a